The Importance of Sociological Engagement in Public Policy - Ghimire, Dipesh Kumar (KMC Research Journal, 2017)
Some scholars believe that it is none of the business of sociology or social science to address social problem and formulate public policy. Lynd (1939) and Hempel (1965) argue that Sociology cannot contribute to setting the public policy and they also believes that the sociology cannot give important contribution in policy process. Is sociology cannot contribute in public policy? This article is especially focused in searching the answer one this question. This article argues that sociological engagement has been advancing gradually in public policy. Sociology has been playing an important role in solving the subjects of public concerns legally and addressing the subject of public interests in an appropriate way.